Application of 3D hologram technology combined with reciprocal style to learn some fundamental boxing skills. - Ahmed Hassan Rakha (PLoS ONE, 2023)
The use of 3D Hologram Technology (3DHT) in teaching and learning has many advantages, such as attracting students' attention, reducing cognitive load and self-effort, and improving spatial awareness. In addition, a number of studies have confirmed that the reciprocal teaching style is effective in teaching motor skills. Thus, the current study aimed to investigate the effectiveness of reciprocal style when combined with 3DHT in learning some fundamental boxing skills. A quasi-experimental design was used by creating two experimental and control groups. For the experimental group, the reciprocal style is combined with 3DHT to teach some fundamental boxing skills. In contrast, the control group is taught a program based on a teacher command style. Pretest-posttest designs were made for the two groups. The sample consisted of 40 boxing beginners aged 12 to 14 who were enrolled in the 2022/2023 training season at Port Fouad Sports Club in Port Said, Egypt. The participants were randomly divided into two experimental and control groups. There were homogenized based on age, height, weight, IQ, physical fitness, and skill level. The results showed the experimental group achieved a higher skill level due to the combination of 3DHT and a reciprocal style in compared to the control group, which relied solely on the teacher's command style,. Due to this, it is imperative to utilize hologram technology as a pedagogical resource to enhance the learning process and combine it with teaching strategies that support active learning.